Careless love : a DCI Banks novel - Robinson, Peter, 1950- (Robinson, Peter, 1950- Inspector Banks series., 2019)
Two suspicious deaths challenge DS Alan Banks and his crack investigative team. A young local student<U+2019>s body is found in an abandoned car on a lonely country road. The death looks like suicide, but there are too many open questions for Banks and his team to rule out foul play. The victim didn<U+2019>t own a car. She didn<U+2019>t even drive. How did she get there? Where<U+2014>and when<U+2014>did she die? Did someone move her, and if so, why? A man in his sixties is found dead in a gully up on the wild moorland. He is wearing an expensive suit and carrying no identification. Post mortem findings indicate that he died from injuries sustained during a fall. Was it an accident<U+2014>did he slip and fall? Or was he pushed? Why was he up there? And why are there no signs of a vehicle near where he fell? As the inconsistencies multiply and the mysteries surrounding these two cases proliferate, a source close to Annie reveals a piece of information that shocks the team and impacts the investigations. An old enemy has returned in a new guise<U+2014>a nefarious foe who will stop at nothing, not even murder, to get what he wants. With the stakes raised, the hunt is on. But will Banks be able to find the evidence to stop him in time?